Prevalence and associated risk factor of hypertension among individuals of age 18-59 years in South-eastern Nepal: A cross-sectional study - Pyakurel, Prajjwal; Yadav, Deepak Kumar; Thapa, Jeevan; Thakur, Nishant; Sharma, Pramita; Koirala, Niraj; Yadav, Suraj Kumar; Chaurasia, Akanksha; Sharma, Sumit; Thapa, June; et al. (Nepalese Heart Journal, 2019)
Background: Hypertension is one of the major risk factors for the rising burden of cardiovascular diseases (CVDs) in developing region. It has also been recognized as one of the major public health problems in the developing countries since the early seventies and the rate is increasing not only in urban areas but in rural areas with low socio-economic condition. Methods: A cross sectional study was conducted in Jogidaha Village Development Comittee(VDC) and Triyuga Municipality of Udaypur district of South-Eastern Nepal. A total of 430 participants of age 18-59 years were selected. Semi-structured questionnaire (WHO NCD STEPS instrument) was used to collect information on demographic variables and associated risk factors with use of show cards. Clinical and anthropometric measurement were done. Primary outcome was prevalence of hypertension. Bivariate and multivariate analysis were performed to show strength of association among various risk factors with hypertension. Results: The prevalence of hypertension was found to be 25.1%. Prevalence of overweight and obesity was found to be 49.8%. Hypertension was significantly associated with age (AOR=1.09, CI=1.05-1.10) and gender (male >female; AOR= 2.12,CI =1.22-3.68). Similarly, increased waist-hip ratio(7.12; CI 2.87-17.67),alcohol consumption(OR=2.82,CI=1.77-4.52), and use of tobacco products (OR =1.8,CI=1.02-3.20) showed significant association with hypertension. Conclusion: There is high prevalence of hypertension in rural districts of South-Eastern Nepal. A community-based preventive approach with early detection and treatment and life-style modification is needed to reduce the burden of disease and make sustainable changes.